Gender Equality and Social Inclusion (GESI) for Strengthening Disaster Resilient Village - Yumarni, Tri; Sulistiani, Lilis Sri; Idanati, Rukna; Gunarto, Guntur (JPAS (Journal of Public Administration Studies), 2021)
Gender equality and social inclusion (GESI) is essential to ensure gender equality and to achieve sustainable Disaster Risk Reduction (DRR). The implementation of decentralisation reform in developing countries has transferred roles of implementing DRR program to lower level of government including to community or village government. Hence, effective strategies to mainstream GESI in DRR activities in the community or village government is important to promote gender equality and to achieve sustainable development. However, what key issues and effective strategies to mainstream GESI in the lower level of community or village has not well-documented in developing countries. This study aims to identify key issues and GESI strategies for strengthening disaster resilient village based on existing literature in developing countries. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was used to identify GESI strategies for strengthening disaster resilient village in the existing literature. We able to find 142 studies related to GESI and disaster risk reduction in community level which published on SCOPUS, Web of Science, and Med Line between 2009 and 2019. From 142 studies we select 10 studies which are strongly relevant with the aim of this study. Five key issues are identified such as low human capital, patriarchal culture, resistance from traditional society, weak GESI institution and poor governance, and lack capacity of policy makers and implementers. There are four key GESI strategies area for strengthening disaster resilient in community level: (1) Organizational, (2) Capacity, (3) Operational, and (4) Resources. In the organizational area, the main strategy is provision of GESI sensitive policies and practices. In the capacity area, the main strategy is capacity development and lesson learning in the community disaster resilient program. In the operational area, the main strategy is embedding GESI in all phases of the community disaster resilient program. In the resources area, the main strategy is mobilizing funding and GESI expertise in the community disaster resilient program.